Character Study: Studying The Personalities of Two Ghibli Characters Facing Humans’ Destructive Behaviors Towards the Ecosystem (Universitas Pendidikan Indonesia, 2025)
As forests are considered the earth’s lungs and are a source of habitat and life for various biodiversity, deforestation by humans which threatens the survival of forests has become an urgent worldwide environmental issue. Hence, the United Nations designed SDG 15: Life on Land where countries were urged to collaborate to protect and restore forests, encourage the use of land ecosystems through sustainable forest management, fight desertification, stop and reverse land degradation, and stop the loss of biodiversity. One form of implementation is through social criticism with films. Hayao Miyazaki, a founder of the Ghibli animation studio, is famous for making films that highlight environmental themes and the importance of maintaining balance between humans and nature. Thus, the characters in Ghibli's films are known to be pro-nature and try to protect it from destruction, like San from 'Princess Mononoke' and Nausicaa from 'Nausicaa: The Valley of The Wind'. San and Nausicaa each fight to save the ecosystem around them from humans' destructiveness. However, they show different attitudes when achieving their goals. Using qualitative methods of literary psychology, it was found that San preferred to fight alone with violence because she was raised with minimal understanding of empathy and acceptance. Meanwhile, Nausicaa, who grew up full of compassion and peace, was more open to the help of others and fought diplomatically. Both ways of fighting are not wrong, have their pros and cons, and are embedded in the personality and life journey of each character.